1993
DOI: 10.1073/pnas.90.20.9649
|View full text |Cite
|
Sign up to set email alerts
|

Increased amyloid beta-peptide deposition in cerebral cortex as a consequence of apolipoprotein E genotype in late-onset Alzheimer disease.

Abstract: Amyloid -peptide (AP) deposition in senile plaques and cerebral vessels is a neuropathological feature of Alzheimer disease (AD). We examined the possibility that commonly observed variability in Af8 deposition in late-onset AD might be related to apolipoprotein E genotype (APOE gene; the two most common alleles are 3 and 4), since APOE4 is a susceptibility gene for late-onset AD and apolipoprotein E interacts strongly with A.8 in vitro. In an autopsy series of brains of late-onset AD patients, we found a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
716
4
14

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,361 publications
(781 citation statements)
references
References 34 publications
47
716
4
14
Order By: Relevance
“…Carriers of the APOE*4 allele (APOE*4+) have an increased risk of developing mild cognitive impairment (MCI) and AD (11,50,66) and appear to have increased pathologic burden (54,67). Imaging with PET and SPECT lend support to the hypothesis that the APOE*4 allele worsens AD, with both increased (29,39) and decreased (17,35,39,51) resting metabolism being reported in demented APOE*4 carriers as compared to demented non-carriers.…”
Section: Introductionmentioning
confidence: 90%
“…Carriers of the APOE*4 allele (APOE*4+) have an increased risk of developing mild cognitive impairment (MCI) and AD (11,50,66) and appear to have increased pathologic burden (54,67). Imaging with PET and SPECT lend support to the hypothesis that the APOE*4 allele worsens AD, with both increased (29,39) and decreased (17,35,39,51) resting metabolism being reported in demented APOE*4 carriers as compared to demented non-carriers.…”
Section: Introductionmentioning
confidence: 90%
“…It was first proposed that apoE was an Ab-binding protein in the brain that induces a pathological b-sheet conformational change in Ab (Wisniewski and Frangione 1992). Pathological studies showed a positive correlation between plaque density and 14 allele dose in AD patients at autopsy (Rebeck et al 1993;Schmechel et al 1993). Although some studies reported conflicting findings (Benjamin et al 1995;Heinonen et al 1995), a large autopsy study strongly suggested that 14 dosage is associated with increased neuritic plaques in AD (Tiraboschi et al 2004).…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%
“…The apoE genotype is associated with Alzheimer's disease (Schmechel et al, 1993;Poirier et al, 1993;Poirier, 1994). Recently, it was reported that increasing the cholesterol content in cell culture reduced levels of soluble amyloid precursor protein (Bodovitz and Klein, 1996).…”
Section: Binding Of Lipids Labeled By Different Fluorophores To Aggrementioning
confidence: 99%